Luminescent polymer electrolytes based on chitosan and containing europium triflate - Alves, Raquel Diana Carneiro (2016)
Solid polymer electrolytes based on chitosan and europium triflate were prepared by solvent casting and they were characterized by X-Ray diffraction, scanning electron microscopy (SEM), atomic force microscopy (AFM) and photoluminescence spectroscopy. The X-Ray diffraction exhibit that the samples were essentially amorphous with organized regions over the whole range of the salt content studied. The AFM analysis demonstrates that the smoother sample has roughness of 4.39 nm. Surface visualization through SEM revealed good homogeneity without any phase separation for more conductive samples and the less conductive showed some imperfections on the surface. The emission and excitation spectra display the characteristic bands of Eu(CF3SO3)3 in addition to broadbands corresponding to the polymer host. The excited state 5D0 lifetime values range from 0.29 – 0.37 ms for the studied samples.